Ecological self-determination of Jesus in the Gospel according to St. John - Najda, Andrzej Jacek (Studia Ecologiae et Bioethicae, 2008)
Jesus often says in John's Gospel that he has come to fulfill the will of the Father (John 4, 34; 6, 38) and to reveal himself as the Son of God. If he uses a revelatory formula that comes from the Old Testament, he presents himself as God. To describe his mission of giving people eternal life, Jesus uses images taken from nature that are well known and understood by his listeners. He describes himself as "the light of the world" (John 8, 12), "the gate" (John 10, 7. 9), "the good shepherd" (John 10, 11. 14) and "the vine" (John 15, 1-5). ). Jesus does this to lead people to faith and penance, that they "may have life and have it abundantly" (John 10, 10).